Impact of COVID-19 on flu vaccination among pregnant women in a Teaching Hospital in Rome: Lorenza Nachira. (25th October 2022) - Nachira, L; Bruno, S; Carducci, B; Villani, L; Pascucci, D; Quaranta, G; Damiani, G; Federico, B; Lanzone, A; Laurenti, P
Abstract: Background: According to WHO, UNICEF, GAVI and the Sabin Vaccine Institute data, the COVID-19 pandemic caused the disruption of routine vaccinations in at least 68 countries. In March '20, the WHO published a guide to help countries continuing their provision safely to prevent unnecessary visits and hospitalizations: especially flu vaccination is paramount to reduce respiratory illnesses and their burden on healthcare systems. For the flu season 2021-22, the Italian Ministry of Health recommended prioritizing flu vaccination for pregnant women. This study aims at comparing flu vaccination rates between pre-pandemic and pandemic periods in pregnant women attending a birthing preparation course at the Fondazione Policlinico Universitario A.Gemelli IRCCS (FPG) in Rome. Methods: A repeated cross-sectional study was carried out in FPG during two flu epidemic seasons (October '19-January '20 and September '20-January '21), when two different cycles of birthing preparation courses were held (face-to-face and online, respectively). Pregnant women and their partners attending them were offered flu vaccination at FPG. A χ2 test was performed to compare vaccination rates, with statistical significance set at p = 0.05. Results: In 2019-20, 48 out of 119 women and 39 men out of 119 attending the course accepted flu vaccination, while in 2020-21 they were respectively 88 out of 317 and 89 out of 317. Overall vaccination compliance among pregnant women was significantly higher in 2019-20 than in 2020-21 (40.3% and 27.8% respectively, p = 0.012), while the difference was not significant among their partners (32.8% and 28.1% respectively, p = 0.337). Conclusions: The COVID-19 pandemic negatively affected flu vaccination adherence among the pregnant women involved. Fear of contagion and access to facilities closer to their home could be potential key drivers. These results represent an important warning on flu vaccination attitudes during the pandemic: more actions are needed to improve compliance. Key messages:  COVID-19 might have hindered access to immunization services for at-risk populations, such as that of pregnant women.  From a Public Health point of view, more actions are needed to harmonize interactions between hospitals and local national health services to improve vaccination compliance.